Knowledge, Attitude, and Practices (KAPs) of Community Pharmacists Regarding COVID-19: A Cross-Sectional Survey in 2 Provinces of Pakistan. (16th October 2022) - Muhammad, Khayal; Saqlain, Muhammad; Muhammad, Gul; Hamdard, Ataullah; Naveed, Muhammad; Butt, Muhammad Hammad; Khan, Siraj; Ismael, Najlaa Saadi; Khan, Zakir; Karatas, Yusuf
Abstract: Objective: The 2019 coronavirus disease (COVID-19) is a global pandemic with no therapy, and pharmacists being a part of the health care system have a vital role in the management of COVID-19. The purpose of this study is to assess the knowledge, attitude, and practices of community pharmacists (CPs) regarding COVID-19. Method: An online survey was conducted among 393 CPs in 2 provinces of Pakistan during the lockdown period. A validated questionnaire (Cronbach's alpha, 0.745) was used for data collection. All statistical analyses were analyzed by using SPSS, version 21 (IBM Corp, Armonk, NY). Results: Among 393 participants, 71.5% (n = 281) had good knowledge, 44% (n = 175) had a positive attitude, and 57.3% (n = 225) had good practices regarding COVID-19. Social media (45.29%, n = 178) were reported as the main source to seek information of COVID-19. Good knowledge, age ≥ 26 years, and a PhD degree level were the substantial determinants ( P = < 0.05) of a good attitude. Similarly, a CP with experience of > 5 years, a PhD degree, good knowledge, and a good attitude has higher odds of having good practices as compared with reference categories ( P = < 0.05). Conclusion: In short, a majority of the CPs had good knowledge but had a poor attitude and practice toward the management of COVID-19. Standard-structured educational and counseling programs for CPs regarding COVID-19 are needed for effective management.